2019
DOI: 10.1002/ddr.21567
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Nrf2 signaling by sitagliptin and quercetin combination against β‐amyloid induced Alzheimer's disease in rats

Abstract: The objective of this study was to evaluate the neuroprotective effect of sitagliptin (Sita), quercetin (QCR) and its combination in β‐amyloid (Aβ) induced Alzheimer's disease (AD). Male Sprague–Dawley rats, weighing between 220 and 280 g were used for experiment. Rats were divided into 5 groups (n = 10) and the groups were as follows: (a) Sham control; (b) Aβ injected; (c) Aβ injected + Sita 100; (d) Aβ injected + QCR 100; and (e) Aβ injected + Sita 100 + QCR 100. Cognitive performance was observed by the Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 39 publications
(48 reference statements)
2
51
0
Order By: Relevance
“…Studies have reported translocation of Nrf2 from the cytosol to the nucleus, where it activates antioxidative enzymes, such as HO-1, and produces a notable antioxidative response to counteract escalated ROS-induced oxidative stress and protect against oxidative stress (Loboda et al, 2016;Xu et al, 2019). The Nrf2/HO-1 signaling pathway is considered as a protective molecular mechanism in several pathological processes, particularly oxidative stress, and this pathway is also involved in several neurodegeneration diseases, including AD and PD (Tufekci et al, 2011;Li Y. P. et al, 2019). Levels of Nrf2 localized to the nucleus and the expression level of HO-1 were both significantly higher in cells treated with DDT, the activation of Nrf2 we observe may in part be mediated via Akt, increasing antioxidant defenses ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported translocation of Nrf2 from the cytosol to the nucleus, where it activates antioxidative enzymes, such as HO-1, and produces a notable antioxidative response to counteract escalated ROS-induced oxidative stress and protect against oxidative stress (Loboda et al, 2016;Xu et al, 2019). The Nrf2/HO-1 signaling pathway is considered as a protective molecular mechanism in several pathological processes, particularly oxidative stress, and this pathway is also involved in several neurodegeneration diseases, including AD and PD (Tufekci et al, 2011;Li Y. P. et al, 2019). Levels of Nrf2 localized to the nucleus and the expression level of HO-1 were both significantly higher in cells treated with DDT, the activation of Nrf2 we observe may in part be mediated via Akt, increasing antioxidant defenses ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…They were Aβ-injection, lipopolysaccharide (LPS)-induced, pentylenetetrazole (PTZ)-induced, senescence accelerated mouse (SAM), and APP/PS1/tau-transgenic AD models. The Aβ injection model can induce Aβ accumulation and deposition in the brain, but as an acute toxicity model it cannot reproduce the progressive neurodegeneration process [18]. The drug-induced models (LPS and PTZ) display neurodegeneration and cognitive impairments, but they lack AD-related histological hallmarks [13,14].…”
Section: Different Animal Modelsmentioning
confidence: 99%
“…et al [17] reported that quercetin treatment strongly prevented Aβ aggregation and partially decreased hyperphosphorylated tau in the CA1 region of the hippocampus and in the amygdala, without changes in the entorhinal cortex of AD mice. Li Y. et al [18] showed that quercetin treatment to AD rats reduced the β-amyloid accumulation in the CA1 region of hippocampus.…”
Section: Neuroprotective Mechanisms Analysismentioning
confidence: 99%
See 2 more Smart Citations